Metacognition via creative writing: dynamic theories of learning support habits of the mind in 21st century classrooms. Issue 3 (3rd July 2017) - Howe, Lori; Wig, Ann Van
ABSTRACT: The focus of this article is the exploration of theories of learning associated with creative writing workshop pedagogy, including transformative, reflective, and experiential learning theories, and reflexivity theory. This exploration of multiple theories of creative learning situates the creative writing workshop model at the intersection of pedagogies supporting metacognition, transformative education, identity development, creativity, and critical thinking, across multiple demographics of writing students.